Computer-aided design of thermoelectric microcalorimetric sensors - Kobylianskyi, R.R.; Lysko, V.V.; Boychuk, V.V. (Journal of Thermoelectricity, 2024)
The paper deals with the design and development of thermoelectric microcalorimetric sensors for use in low-power reaction chambers. The physical and mathematical aspects of the sensitivity and response speed of sensors made of Bi-Te semiconductor material and copper-constantan-based metal legs with appropriate geometric arrangements of the legs are investigated. The paper presents a computer design algorithm, depicted as a block diagram, and also demonstrates the development of a program for automating the design process with subsequent implementation of the software. Practical examples of the development and analysis of the calculated parameters for two types of sensors are presented to identify their advantages in measuring low thermal powers and fast processes, respectively.